1974
DOI: 10.1002/bip.1974.360130411
|View full text |Cite
|
Sign up to set email alerts
|

13C nmr study of the helix–coil transition of poly‐N5‐(3‐hydroxypropyl)‐L‐glutamine

Abstract: SynopsisThe helix-coil transition of poly-NS-(3-hydroxypropyl)-~..-glutamine in methanol-water solutions has been observed using 13C nuclear magnetic resonance. Two signals appear in the a-CH region in the course of the transition; this is in contrast with previous proton magnetic resonance experiments carried out on this polymer in the same solvent system. 765

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1974
1974
2004
2004

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Another peak appears at 57.2 and 176.9 ppm for C and C 0 =O, respectively, at CD 3 OD 60 % where the random coil to helix transition occurs. 34 The intensity of these peaks increases rapidly with increase of CD 3 OD content. It was further observed that the transition region of coil to helix shifts to higher CD 3 OD contents with increase of the temperature.…”
Section: Resultsmentioning
confidence: 94%
“…Another peak appears at 57.2 and 176.9 ppm for C and C 0 =O, respectively, at CD 3 OD 60 % where the random coil to helix transition occurs. 34 The intensity of these peaks increases rapidly with increase of CD 3 OD content. It was further observed that the transition region of coil to helix shifts to higher CD 3 OD contents with increase of the temperature.…”
Section: Resultsmentioning
confidence: 94%
“…Further evidence that polydispersity is the basis for double peaks has been presented by Di Blasi and Verdini. 25 They have shown that lowmolecular-weight poly[N5-(3-hydroxy propy1)~-glutamine] in water/ methanol mixtures exhibits peak doubling in the carbon-13 nmr spectrum. On fractionation, the double-peak character is reduced.…”
Section: Resultsmentioning
confidence: 99%